A question of priorities : democratic reforms and economic recovery in postwar Germany : Frankfurt, Munich, and Stuttgart under U.S. occupation, 1945-1949 - Boehling, Rebecca L., 1955- (Monographs in German history, 1996)
Over the last few years, there has been a noticeable increase in studies on the postwar period of Germany, reflecting the crucial importance of these years for an understanding of the developments in the two Germanys. With her study of U.S. occupation policy and its effects on German social and political developments in Frankfurt, Munich, and Stuttgart, Rebecca Boehling offers a most valuable contribution to this debate. She examines the decisions made by the U.S. Military Government regarding German municipal personnel from the first year of the occupation, when all city officials were appointed directly by Military Government or with its explicit approval, through the first postwar municipal elections in 1946 and 1948, when democratic self-government was gradually restored.